View of Vienna from the north side of the Danube - Berry (engraver):::Creator::::::::::::; Craig (artist):::Contributor:::::::::::: (Nuttall Fisher & Dixon; Liverpool; United Kingdom)
Engraving of Vienna from the north side of the Danube River